The Three Hundred Project: Substructure in hydrodynamical and dark matter simulations of galaxy groups around clusters. Issue 1 (11th January 2021) - Haggar, Roan; Pearce, Frazer R; Gray, Meghan E; Knebe, Alexander; Yepes, Gustavo
ABSTRACT: Dark matter-only simulations are able to produce the cosmic structure of a Lambda cold dark matter universe, at a much lower computational cost than more physically motivated hydrodynamical simulations. However, it is not clear how well smaller substructure is reproduced by dark matter-only simulations. To investigate this, we directly compare the substructure of galaxy clusters and of surrounding galaxy groups in hydrodynamical and dark matter-only simulations. We utilize t het hreeHundred project, a suite of 324 simulations of galaxy clusters that have been simulated with hydrodynamics, and in dark matter-only. We find that dark matter-only simulations underestimate the number density of galaxies in the centres of groups and clusters relative to hydrodynamical simulations, and that this effect is stronger in denser regions. We also look at the phase space of infalling galaxy groups, to show that dark matter-only simulations underpredict the number density of galaxies in the centres of these groups by about a factor of four. This implies that the structure and evolution of infalling groups may be different to that predicted by dark matter-only simulations. Finally, we discuss potential causes for this underestimation, considering both physical effects, and numerical differences in the analysis.